2007
DOI: 10.1086/512202
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Haplogroup N9a Confers Resistance against Type 2 Diabetes in Asians

Abstract: Because mitochondria play pivotal roles in both insulin secretion from the pancreatic beta cells and insulin resistance of skeletal muscles, we performed a large-scale association study to identify mitochondrial haplogroups that may confer resistance against or susceptibility to type 2 diabetes mellitus (T2DM). The study population comprised 2,906 unrelated Japanese individuals, including 1,289 patients with T2DM and 1,617 controls, and 1,365 unrelated Korean individuals, including 732 patients with T2DM and 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
177
7
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 195 publications
(190 citation statements)
references
References 27 publications
4
177
7
1
Order By: Relevance
“…The association with haplogroup J was supported by a study in a white Brazilian population, which also found an association with haplogroup T [19]. More recently, there has been a report that haplogroup N9a confers resistance to type 2 diabetes in Asians [20]. In the largest association study to date [21], an association between both diabetes disease status and related metabolic traits and common European mitochondrial variants was tested for in several populations of European origin.…”
Section: Introductionmentioning
confidence: 87%
“…The association with haplogroup J was supported by a study in a white Brazilian population, which also found an association with haplogroup T [19]. More recently, there has been a report that haplogroup N9a confers resistance to type 2 diabetes in Asians [20]. In the largest association study to date [21], an association between both diabetes disease status and related metabolic traits and common European mitochondrial variants was tested for in several populations of European origin.…”
Section: Introductionmentioning
confidence: 87%
“…reporting no association between mtDNA haplogroups and EL (Pinos et al ., 2012) but Dominguez‐Garrido and co‐workers finding that the Caucasian haplogroup J (which would be associated with lower mtDNA damage) might confer a higher chance to attain high longevity (85+years) compared with other haplogroups in Northern Spaniards (DomĂ­nguez‐Garrido et al ., 2009). On the other hand, although mtDNA haplogroups D4b2b, D4a, and D5 are not associated with type 2 diabetes (Fuku et al ., 2007), they are linked with EL in Japanese population (Alexe et al ., 2007; Bilal et al ., 2008). We also showed that the mtDNA m.1382A>C polymorphism, which is specific for the ancestor haplogroup D4b2, is associated with EL in the Japanese population (Alexe et al ., 2007).…”
Section: Mitochondrial Haplogroups and Elmentioning
confidence: 99%
“…shtml) and recent reports. [16][17][18][19] Consequently, it is also necessary to distinguish pathogenic mtDNA mutations from mtSNPs.…”
Section: Introductionmentioning
confidence: 99%